Penanganan Anak Temper Tantrum Studi Kasus Di Tk Tq Muhammad Al-Fatih - Nihwan Nihwan; Melina; Irmawati (Universitas Muhammadiyah Metro, 2024)
Abstract This study aims to explore the strategies used by teachers in handling children experiencing tantrums at TQ Muhammad Al Fatih Kindegarten. This case study employs a qualitative approach using observation and in-depth interviews to collect data. The research subjects are childern who frequently have tantrums and the teachers who handle them. The result of the study indicate that teachers implement various effective strategies to calm tantrums, including distraction techniques, consintent boundary setting, and providing emotional support. Teachers also use individualized approaches tailored to each child’s chatacteristics. Additionally, teachers actively engage childern in activities that can divert their attention from sources of frustration. This study suggests the need for further training for teachers in behavior management techniques to handle tantrums effectively and create a more conducive learning environment.